A critical appraisal of brown adipose tissue metabolism in humans. (June 2015) - Blondin, Denis P; Labbé, Sébastien M; Turcotte, Eric E; Haman, François; Richard, Denis; Carpentier, André C
The presence of brown adipose tissue (BAT) in adult humans has been rediscovered through the clinical use of the radioactive glucose analog 18 F-fluorodeoxyglucose with PET. This has led to numerous studies demonstrating cold exposure as the major physiological modulator of BAT activity. These reports also suggested that age, gender, BMI and the presence of diabetes are also important modulators of BAT volume and metabolic activity. Although 18 F-fluorodeoxyglucose PET has provided important information on BAT glucose metabolism, other techniques are being developed and applied to assess other aspects of BAT metabolism. Here, we summarize the current understanding of the pathophysiological functions of BAT in humans and discuss some of the strengths and limitations of the current investigational techniques.